The analgesic and anti-inflammatory effects of zukamu granules, a traditional Chinese medical formulation - Qiang Yin (Taylor & Francis Group, 2019)
Context: Zukamu granule, a traditional Chinese medicine, has shown clinical treatment efficacy. However, the pharmacodynamic effects and possible anti-inflammatory mechanisms of zukamu are still unclear. Objective: To investigate the analgesic and anti-inflammatory effects and possible mechanisms of zukamu granules on acute lung injury. Materials and methods: Kunming mice and Sprague Dawley rats were gavaged with zukamu (1.35, 2.7 and 5.4 g/kg, respectively) or ganmaoling (GMLG; 2.7 g/kg) once a day for 7 d. Dexamethasone treatment (5 mg/kg) were administered only on the last day. Analgesic effects were evaluated through the hot plate test and acetic acid writhing test. The expression of cytokines and proteins was measured in serum and lung tissues to elucidate the efficacy of zukamu against lung injury. Results: Significant analgesic effects were observed at 30 min after zukamu administration at medium and high doses (p < 0.05), but the effect was not obvious at low dose until 60 min post-administration (p > 0.05). Zukamu treatment at all doses notably reduced the lung wet-to-dry (W/D) ratios compared to that of model rats (p < 0.05) and the effect was more evident at high dose compared to those at medium and low doses. The levels of cytokines and proteins in the lung tissues were inhibited by zukamu. Conclusions: Zukamu exhibited analgesic and protective effects against lung injury via regulating NF-κB signalling and inflammatory cytokines. As zukamu granules contain multiple ingredients, further exploration of the mechanisms underlying its analgesic and anti-inflammatory functions were needed.